2016
DOI: 10.3138/ptc.2015-63
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Current Practices of Canadian Physiotherapists in Preventing and Managing Diabetes

Abstract: Purpose: To describe the knowledge, attitudes, and current practices of Canadian physiotherapists in preventing and managing diabetes. Methods: Members of the Canadian Physiotherapy Association were recruited by email to participate in a Web-based survey. The survey contained 40 items in four domains: demographics and education, attitudes and beliefs, current practices, and knowledge of diabetes. A descriptive analysis was completed for all the response variables from the survey. Results: A total of 401 physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Doehring et al 11 surveyed 401 Canadian physical therapists about their knowledge, attitudes, and practice toward DM prevention and management. It transpired that physical therapists were most confident in providing exercise education, but lacked confidence in providing care in crucial areas, including managing secondary complications, glucose level control, and weight management.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Doehring et al 11 surveyed 401 Canadian physical therapists about their knowledge, attitudes, and practice toward DM prevention and management. It transpired that physical therapists were most confident in providing exercise education, but lacked confidence in providing care in crucial areas, including managing secondary complications, glucose level control, and weight management.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, by identifying this clinical gap, they provided some important recommendations, such as providing more education related to DM in entry-level programs, and enhancing continuing physical therapy education opportunities to improve physical therapists’ knowledge of DM. 11 However, these findings may not be generalizable to other physical therapists, particularly in the Kingdom of Saudi Arabia, because of differences in cultural backgrounds, educational systems, and healthcare policies, which may affect physical therapist practices in the Kingdom.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Physiotherapists, however, are some of the most important practitioners in the management of diabetes and its comorbid conditions because they can prescribe exercise to prevent and treat the disease. In an encouraging vein, Doehring and colleagues 1 reported that most respondents believed that preventing and managing diabetes was within their scope of practice. An amazing opportunity awaits those physiotherapists who embrace their role in promoting health and wellness, treating past symptoms, and addressing the pathophysiology of disease.…”
mentioning
confidence: 99%